A mathematical model for location of temporary relief centers and dynamic routing of aerial rescue vehicles. (May 2019) - Alinaghian, Mahdi; Aghaie, Mohammad; Sabbagh, Mohammad S.
Graphical abstract: Highlights: A novel model for location of temporary relief centers and dynamic routing of aerial rescue vehicles. For the first time dynamic tour covering model is presented. An improved hybrid meta-heuristic algorithm based on scatter search and NNS is presented. Results obtained by proposed algorithm are compared with an exact method, SS and GA and analyzed. Abstract: This paper presents a new mathematical model for location of temporary relief centers and dynamic routing of aerial rescue vehicles distributing basic supplies in relief operations. The objective function of the proposed model minimizes the arrival time at the last designated temporary relief center. The proposed model seeks to locate the temporary relief centers in a way that all affected areas get covered by at least one temporary relief center. Considering the importance of quick action amid a post-disaster environment with characteristics such as uncertain demand for relief supplies, inaccurate information regarding victims, aftershocks, and extensively damaged road networks, in the proposed model, location and level of demand are considered to be dynamic, and relief supplies are assumed to be distributed by aerial transport vehicles. According to NP-Hardness of proposed problem, in this paper an improved hybrid metaheuristic algorithm based on scatter search combined with variable neighborhood search is presented. To evaluate the performance of the proposed algorithm, it is tested and compared with an exact method, basic scatter search and genetic algorithm. Results show the good performance of the proposed algorithm.